ANALISIS YURIDIS KASUS HAK ASUH ANAK TSANIA MARWAH: TANTANGAN PERLINDUNGAN HAK IBU DAN ANAK DI INDONESIA - Rofiah, Zulfa (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the case of Tsania Marwah as an illustration of the challenges in implementing legal protection for mothers and children in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches, examining regulations such as Law No. 35 of 2014 on Child Protection, Law No. 1 of 1974 on Marriage, and Article 105 of the Compilation of Islamic Law (KHI). The findings reveal a significant gap between legal norms and actual practice. Although the court awarded child custody to the mother, enforcement of the decision proved difficult due to the absence of a strong enforcement mechanism, lack of strict sanctions for violators, and weak support from law enforcement institutions. Additionally, existing legal provisions fall short in addressing complex custody violations committed by biological parents and do not adequately safeguard the best interests of the child. The study underscores that weak institutional coordination, low public legal awareness, and insufficient governmental commitment are key barriers to the effective implementation of custody rights. Accordingly, this research recommends policy reforms that include strengthening enforcement mechanisms, applying stricter legal sanctions, improving cross-sectoral coordination, and developing sustainable legal education programs for the public.